Characteristics and Physiologic Changes After 4% Albumin Fluid Boluses in a PICU. Issue 1 (January 2022) - Gelbart, Ben; Fulkoski, Nick; Stephens, David; Bellomo, Rinaldo
Abstract : OBJECTIVES: To describe the characteristics, hemodynamic, and physiologic changes after 4% albumin fluid boluses in critically ill children. DESIGN: Retrospective observational study. SETTING: Single-center PICU. PATIENTS: Children in a cardiac and general PICU. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Between January 2017 and May 2019, there were 1, 003 fluid boluses of 4% albumin during 420 of 5, 731 admissions (7.8%), most commonly in children with congenital/acquired heart disease (71.2%) and sepsis (7.9%). The median fluid bolus dose was 10 mL/kg (interquartile range, 5.8–14.6 mL/kg), and its duration 30 minutes (interquartile range, 14.0–40.0 min; n = 223). After the fluid bolus, a significant change in mean arterial pressure (2.3 mm Hg [5.1%], 2.7 mm Hg [5.8%], 2.9 mm Hg [6.1%], and 3.8 mm Hg [8.0%] at 1, 2, 3, and 4 hr, respectively [ p ⩽ 0.001]) only occurred in children less than or equal to 12 months old. A mean arterial pressure response, defined by an increase greater than or equal to 10% from baseline, occurred in 290 of 887 patients (33%) with maximal response at 1 hour. Hypotension at baseline predicted the magnitude of mean arterial pressure increase at 60 (coefficient 24.3 [95% CI, 0.79–7.87]; p = 0.04) and 120 minutes (coefficient 26.1 [95% CI, 2.75–48.2]; p = 0.02). There were no biochemical or hematocrit changes within 4 hours of the fluid bolus. Urine output for the entire cohort was 2 mL/kg/hr at baseline and did not change with the fluid bolus. CONCLUSIONS: Fluid boluses of 4% albumin were common and predominantly in children with cardiac disease and sepsis with a median dose of 10 mL/kg given over half an hour. Such treatment was associated with significant hemodynamic changes only in children less than 12 months old, and we failed to identify an association with urine output. Abstract : Supplemental Digital Content is available in the text.